2012
DOI: 10.1016/j.jval.2012.08.225
|View full text |Cite
|
Sign up to set email alerts
|

PRS4 Evidence Synthesis of Association of HLA-B*1502 Allele and Carbamazepine -Induced Stevens Johnson Syndrome and Toxic Epidermal Necrolysis: A Systematic Review

Abstract: OBJECTIVES:To evaluate Health Related Quality of Life (HRQoL) among general population of Quetta city, Pakistan. METHODS: The study was designed as a questionnaire-based cross sectional analysis. European Quality of Life scale (EQ-5D) was used for assessment of HRQoL. A total of 1500 healthy participants from March 2011 to July 2011, aging 18 years and above were approached. Descriptive statistics were used to describe demographic characteristics of the general population. Percentages and frequencies were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 0 publications
0
51
0
Order By: Relevance
“…The strength of such associations has led to the recommendation to screen for this variant in patients with Asian ancestry before starting treatment [46,47]. However, other studies have failed to find such associations in Japan [48,49] and Europe [50,51].…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…The strength of such associations has led to the recommendation to screen for this variant in patients with Asian ancestry before starting treatment [46,47]. However, other studies have failed to find such associations in Japan [48,49] and Europe [50,51].…”
Section: Anticonvulsantsmentioning
confidence: 99%
“…Notably, we found associations between HLA-B*1502 and OXC-induced SJS in both general population control and OXC-tolerant groups Other OXC-induced pathologies such as TEN are not well studied and, to our knowledge, are confined to studies where SJS and TEN data were pooled (7,11,25). Thus, based on current findings and the previous studies, subjects harboring the allele might develop TEN when given OXC.…”
Section: Discussionmentioning
confidence: 83%
“…Several studies suggested that most cADRs caused by epileptic drugs (e.g., CBZ, phenytoin, lamotrigine) are drug-specific immune responses through human leukocyte antigens (HLAs) (7,8). HLA is a gene group encoding the major histocompatibility complex (MHC) located on chromosome 6 in humans (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…The latter association was first demonstrated in Han Chinese patients, in which 44 with CBZ-induced SJS/TEN were positive for HLA-B*15:02 compared to 3% in the CBZ-tolerant cohort (odds ratio 2504) (7). Subsequent studies have also confirmed this association in Thai, Korean, Malaysian and Indian populations (8). As a result of this suggestive results, the US Food and Drug Administration has recommended prescreening testing for HLA-B*15:02 allele before prescribing CBZ in the ethnic groups at risk (9).…”
Section: Introductionmentioning
confidence: 81%